Crossroads: an evaluation of a transitional housing program for youth - McFarland, Megan Carol (Kansas State University, 2011)
Homelessness is an issue facing numerous communities. Additionally, the increasing number of homeless youth is growing at an alarming rate. One potential solution to combating homelessness is transitional housing programs, and specifically programs aimed at assisting youth. The youth transitional housing program addressed in this research is the Crossroads program located in Lansing, Michigan, serving a tri-county area. This research study evaluates the Crossroads program’s success at preparing youth for independent living. The research questions posed for this study were: 1) What is the Crossroads program doing well to assist youth in transitioning into safe and stable housing? and 2) What does Crossroad’s need to improve upon in order to better help youth prepare for independent living? To answer these questions, data was collected through three one-on-one personal interviews with previous and current Crossroads clients to gather their perspective on the success of the program. Interview participants stated that Crossroads staff is the primary positive aspect of the program. Additionally, interview participants felt the program was good overall and had a positive impact on them, but gave a few suggestions for improvements. Interview responses are summarized and a series of conclusions and recommendations drawn to assist Crossroads in increasing their level of service to future program participants. Recommendations range from beginning the job search earlier, to increasing group activities among clients. Conclusions and recommendations are specifically for the Crossroads program and should not be inferred to be applicable to all youth transitional housing programs.
Keywords: Transitional Housing; Homelessness; Poverty; Homeless Programs; Area Planning and Development (0341); Public Policy and Social Welfare (0630)